Hoitokokouksen äänet : dialoginen analyysi perhekeskeisen psykiatrisen hoitoprosessin hoitokokouskeskusteluista työryhmän toiminnan näkökulmasta - Haarakangas, Kauko (1997)
The context of this study is treatment meeting, which is the basic event in the family and network oriented psychiatric treatment model at Keropudas Hospital in Tornio and in its catchment area in Western Lapland. The aim of the study is to examine conversation in treatment meeting as a dialogical process especially from the viewpoint of the team. The treatment meetings examined have been supervised situations in family therapy training. The treatment meeting conversations which have been analyzed consist of three cases: an outpatient case including seven meetings; an inpatient case with two meetings; and a crisis intervention case which was an admission meeting on the boundary between the hospital and the outpatient treatment. The focus of interest is the activity of the team a) in coupling with the family members and other participants in treatment meeting; b) in generating and maintaining dialogical and polyphonic conversation; c) in evolving new meanings; and d) in using reflective discussion between team members as a therapeutic means. The study was undertaken by using a method called dialogical analysis. The conceptual model of dialogical analysis is based on Bakhtin's theory of dialogism, Maturana's concept of structural coupling and some points of discourse analytic approach. The results of the study indicate that when the meaning systems of the team and of the clients are coupled with each other a new discourse can evolve where the voices of all participants can be in dialogical connection and the symptom-centered discourse of the family life can change into a therapeutic discourse which deals with e.g. resources of the clients and problems of family interrelations in their historical and systemic context. The task of the team is to generate dialogue that promotes potential discourse where the object of consideration can be the themes and meanings which are difficult in the meaning system of the family. The reflective discussion of the team is a therapeutic means that can promote dialogicality and semantic development in treatment meeting. The dialogical action model for the team has been outlined on the ground of the results.